HLA Polymorphisms and Food Allergy Predisposition - Kostara, Maria (J Pediatr Genet, 2020)
Food allergy (FA) is a growing health problem that affects ∼8% of the children worldwide. Although the prevalence of FA is increasing, the underlying genetic mechanisms responsible for the onset of this immune disorder are not yet clarified. Genetic factors seem to play a leading role in the development of FA, though interaction with environmental factors cannot be excluded. The broader network of genetic loci mediating the risk of this complex disorder remains to be identified. The human leucocyte antigen (HLA) has been associated with various immune disorders, including FA. This review aims to unravel the potential associations between HLA gene functions and the manifestation and outcome of FA disorders. Exploring new aspects of FA development with the perspective to improve our understanding of the multifaceted etiology and the complex biological mechanisms involved in FA is essential.